Ramsey numbers for graphs of order four versus connected graphs of order six - Hoeth, Maik; Mengersen, Ingrid (Utilitas Mathematica, 2000)
For all connected graphs G of order six the Ramsey numbers r(K1,3 + e, G) and r(K4 - e, G) are presented up to r(K4 -e, K6).